Toll Collect: Panne von Industrie und Politik. Innovationspolitische Aspekte der geplanten Einführung eines elektronischen Mautsystems in Deutschland. - Fleischer, Torsten; Halbritter, Günter (Deutscher Verkehrs-Verlag, 2004)
Bisher wird die an technischen und organisatorischen Problemen gescheiterte Einführung des technisch anspruchsvollen elektronischen Mautsystems Toll Collect in Deutschland vornehmlich als industriepolitische Panne angesehen. Doch sie offenbart auch innovationspolitische Defizite, die in Deutschland vorliegende politische Rahmenbedingungen für die im Augenblick intensiv diskutierten Innovationen betreffen. difu

Comparative reviews of different countries' innovation strategies concerning the application of telemetry in the field of transport (VT) have shown that infrastructure-based innovations, whose implementation is subject to the creation of an appropriate infrastructure framework, require conceptual-strategic and organizational guidance from a government institution to ensure their successful realization. In Germany, it is accepted that the implementation of innovations is the responsibility of the industrial sector. This includes such a complex task as collecting toll charges in the hope that such a project can somehow be realized. The implementation strategy has been separated from any influence of the 'Executive' and 'Legislative' bodies and thus from any political guidance and examination. The lack of potential state intervention - especially in relation to coordination - has been accepted as the main reason for the problems associated with the implementation of a satellite-guided toll system for trucks. difu
Keywords: Güterverkehr; Lastkraftwagenverkehr; Verkehr; Verkehrspolitik; Autobahn; Gebühr; Innovation; Maut; Public-Private-Partnership